Changes in Diabetes Management during the COVID-19 Pandemic in Trinidad: A Retrospecting Qualitative Study - Shivananda B. Nayak; Daniella Martineau; Geetha Bhaktha; Aaron Martins; Matabadal Karina; Camira M. C. Clashie; Kirdisha M. C. Guire; Andre-Ella Medford; Adell Melville; Hezron Melville (Preventive Medicine: Research & Reviews)
Introduction: Studying the impact of the COVID-19 pandemic impact on diabetes care is crucial for identifying the barriers and developing strategies to overcome them. Methodology: This retrospective qualitative study included diabetic patients from clinics in Eastern Regional Health Authority and private medical institutions, as well as private citizens. Participants were selected through snowball sampling, and data were collected using a 29-item questionnaire. Results: The study had 34.2% males, 65.8% females of those 71.0% were living with diabetes for <10 years. In terms of diabetes management, 68.4% attended clinic/hospital physically. Regarding waiting time, 43% experienced an increase, 7% saw a decrease and 50% noticed no change. Managing diabetes during the pandemic, 50% had no problems. Access to medical care changed for 48.4% of participants, while 6.4% did not seek care. Access to medication remained unaffected for most with 26.3% experienced reduced access and 5.3% saw improvement. Conclusion: This adaptability of preventive and clinical care interventions is crucial for ensuring continuous and effective care during a public health crisis.